School meals in Aracaju: a perception of family members after the Covid-19 pandemic (Research, Society and Development, 2023)
Introduction: After the onset of the pandemic by the new coronavirus, children were subjected to social isolation. This measure resulted in a biopsychosocial impairment in the students, since it generated an unfavorable environment for the preservation of a healthy lifestyle and diet. Thus, with the increased consumption of inappropriate foods for this population, it leads to an increase in the rate of overweight and chronic non-communicable diseases. Objective: To evaluate the impact of the Covid-19 pandemic on the diet of children in the school age group through the perception of family members. Methods: Cross-sectional, retrospective and analytical study carried out in Aracaju, Sergipe, with children aged 5 to 9 years, from 2022 to 2023. Data were collected through an electronic form using Google Forms. Results: Regarding eating habits after the implementation of the Covid-19 pandemic, 44.8% of the participants stated that they had changed. Of these changes, 80.8% proved to be a negative change. Only 8.6% of children do not consume processed foods and 53.4% of participants stated that there was an increase in intake after the pandemic. There was weight gain in 41.4% of the total number of children analyzed, with 69.7% related to food. Conclusion: The pandemic caused by the new coronavirus had a negative influence on the quality of children's food. In Aracaju, there was an increase in the consumption of industrialized products, promoting consequences that remain even after this period.